Perlindungan Hukum Harta Bawaan Debitur Pasca Perceraian - Fitriyah, Puspa (Al-Wasathiyah: Journal of Islamic Studies, 2022)
The problem of debt is included in the field of personal status, where marriages are carried out between spouses, which as a result of the law of debt become a burden to be borne together from marriage agreements between citizens, especially related to the distribution of joint assets. How is the legal liability of debtors to creditors in the final period of marriage? and How is the legal protection for the debtor's innate property? Regarding the marriage agreement, it is regulated in Article 29 of Law Number 1 of 1974 concerning Marriage. This is because of the agreement made between the husband and wife both regarding joint property after marriage and the child's guardianship rights as well as the citizenship status of the child and each party. The method used in this research is normative juridical and empirical juridical research which is analyzed using legal certainty theory and legal liability theory. From the results of the research. Events that often occur in the field of debt, debt repayments that must be paid by the debtor are often not as agreed. In the legal certainty of customer credit guarantees on objects of land and building mortgages, there is a decrease in the appraisal value by the bank, but the binding of credit guarantees with mortgages is carried out if a customer or debtor obtains credit facilities from the bank. Divorce is an abolition of marriage accompanied by a judge's decision. or at the will of one of the parties, both husband and wife, through the submission of a claim by one of the parties to the marriage.